Book Review: Cristina B. Gibson and Susan G. Cohen, Virtual Teams That Work: Creating Conditions for Virtual Team Effectiveness. Issue 4 (December 2018) - Krishnan, Shalini
Cristina B. Gibson and Susan G. Cohen, Virtual Teams That Work: Creating Conditions for Virtual Team Effectiveness, 2003, San Francisco, CA: Jossey-Bass, 436 pp., ₹2, 162.09. ISBN: 0-7879-6162-0.